The Retail Internationalization Dynamics in Central and Southeastern Europe (Vallis Aurea, 2023)
One of the dominant economic trends in transition countries of Central and Southeastern Europe (SEE) is the internationalization of retailing. The countries in this region represent a receptive market for large retailers from developed countries. The aim of this paper is to fill the existing gap in the contemporary literature regarding retail internationalization in particular geographical area. Therefore, firstly the paper explains the very concept and motives of retail internationalization. Subsequently, based on the analysis of secondary data on the world's largest retailers, it gives an insight into the current state of retail internationalization in Croatia, Bosnia and Herzegovina, Serbia and Slovenia, and discusses the dynamics of internationalization of retailing from 2004 until today. Finally, some indications of problems related to future retail development in Central and Southeastern Europe are explained.